1992
DOI: 10.1111/j.1432-1033.1992.tb16588.x
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin stimulation of liver parenchymal cell phosphofructokinase activity requires nonparenchymal cells

Abstract: The rate of carbohydrate flux through phosphofructokinase (measured as the rate of [3-3H]glucose detritiation) was increased fourfold in rat liver parenchymal cells incubated with conditioned mediuni from lipopolysaccharide-stimulated adherent liver non-parenchymal cells. The rate was not affected in parenchymal cells incubated either with lipopolysaccharide directly or with conditioned medium from non-stimulated non-parenchymal cells. The stimulation of carbohydrate flux through phosphofructokinase by conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

1994
1994
1995
1995

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
(8 reference statements)
1
4
1
Order By: Relevance
“…In contrast with previous studies [6,8], the work of Miller et al [13] has suggested that the increase in PFK-1 flux following endotoxin treatment and the inhibition of gluconeogenesis can be dissociated, with the stimulation of PFK-1 flux being independent of both cytokine action and lowered glucose synthesis.…”
Section: Controlcontrasting
confidence: 59%
See 3 more Smart Citations
“…In contrast with previous studies [6,8], the work of Miller et al [13] has suggested that the increase in PFK-1 flux following endotoxin treatment and the inhibition of gluconeogenesis can be dissociated, with the stimulation of PFK-1 flux being independent of both cytokine action and lowered glucose synthesis.…”
Section: Controlcontrasting
confidence: 59%
“…Gram-negative bacterial infection or treatment of animals with bacterial endotoxin is characterized by profound alterations in glucose homoeostasis, typically an initial transient hyperglycaemia followed by a prolonged and frequently fatal hypoglycaemic phase [1][2][3][4][5][6][7][8][9]. During the initial phase there is a pronounced mobilization of hepatic glycogen [10-12] and increased flux through 6-phosphofructo-1 -kinase [8,13], whereas in the latter phase hepatic glucose synthesis from lactate, pyruvate and a number of other substrates is decreased [1][2][3][4][5][6][7][8][9]. We have suggested that the inhibition of gluconeogenesis results primarily from a lowered substrate flux through phosphoenolpyruvate carboxykinase, with the increase in 6-phosphofructo-1-kinase activity being of secondary importance [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For mammals, emphasis is laid on the role of sessile or tissue macrophages as intermediates in the bidirectional communication between the immune and endocrine systems. This is illustrated by the mechanism of action of LPS on liver metabolism (Miller et al 1992), on pituitary hormone release (Spangelo and MacLeod 1990) and on gonadal function (Sun et al 1993). Fish are particularly insensitive to the toxic effects of LPS (Wedemeyer el al.…”
Section: Discussionmentioning
confidence: 99%